Design and Development of an E-learning Information System Using the Laravel Framework at SMA Negeri 3 Medan - Dery Antoro; Sri Wahyuni (Yayasan Sinergi Multidimensi Kreatif, 2024)
This research discusses the design and development of an e-learning information system using the Laravel framework specifically for SMA Negeri 3 Medan. The system aims to address the growing need for a more accessible and engaging learning platform, adapting to the increasing influence of technology in the field of education. The development process employs a structured and comprehensive methodology, incorporating thorough needs analysis, detailed system design, implementation using the robust Laravel framework, and rigorous testing procedures. The resulting e-learning system offers a wide range of features, including interactive learning modules, online assessments, and robust communication tools, all tailored to enhance the overall learning experience for the students and teachers at SMA Negeri 3 Medan. This innovative system is expected to contribute significantly to the creation of a more effective, modern, and technology-driven learning environment within the school, providing a seamless and user-friendly platform for enhanced teaching and learning outcomes.